2013
DOI: 10.2466/26.10.pms.117x12z2
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Weight-Bearing and Effort Distribution during Sit-to-Stand in Individuals Post-Stroke

Abstract: The objectives were to assess whether individuals who are poststroke can rate their perceived knee effort distribution during sit-to-stand tasks in various foot positions, to quantify their errors of perception and to compare these to their errors in weight-bearing perception. Weight-bearing distribution was assessed in hemiparetic participants (N = 19) using a force platform. Electromyographic (EMG) data normalized to maximal EMG values were used to quantify knee effort distribution. The difference between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, the study by Briè re et al [43] has revealed that patients are better at perceiving their WB than their knee efforts. Thus, the focus should be on asking the patients to increase the weight under the affected foot and not to increase their effort [43].…”
Section: Rehabilitation Strategies Used To Improve Stsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the study by Briè re et al [43] has revealed that patients are better at perceiving their WB than their knee efforts. Thus, the focus should be on asking the patients to increase the weight under the affected foot and not to increase their effort [43].…”
Section: Rehabilitation Strategies Used To Improve Stsmentioning
confidence: 97%
“…However, the study by Briè re et al [43] has revealed that patients are better at perceiving their WB than their knee efforts. Thus, the focus should be on asking the patients to increase the weight under the affected foot and not to increase their effort [43]. Placing the affected foot posterior to the unaffected foot will help increase the weight taken by the affected limb [9,18,24].…”
Section: Rehabilitation Strategies Used To Improve Stsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Brière et al [2], it is better to perceive the affected side than to increase the knee effort. When patients first attempt to stand from a sitting position following a stroke, they tend to load their weight on the less-affected side due to non-use syndrome [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a tendency toward asymmetric weight-bearing during STS because patients usually support themselves with the non-paretic foot [2]. Engardt and Olsson [3] reported that, following stroke, patients performed more asymmetric weight-bearing with the less-affected leg.…”
Section: Introductionmentioning
confidence: 99%